(untitled) (Jahangirnagar University Journal of Biological Sciences, 2016)
Effect of exotic tree plantation on floristic composition and phytodiversity status of Rema-Kalenga wildlife sanctuary of Bangladesh was studied. A total of 309 vascular plant species under 245 genera belonging to 83 families were found to constitute the vascular flora of the studied area. The maximum number of species (298) with the highest Shannon-Weiner diversity index value (3.882±0.090) was recorded from natural forest, which was followed by 194 and 165 plant species with 3.441±0.205 and 3.398±0.103 diversity index values recorded from Tectona and Acacia plantation sites respectively. The minimum number of plant species (142) with the lowest diversity index value (2.999±0.152) was recorded from Eucalyptus plantation site. The collected data on the selected forest sites of Rema-Kalenga wildlife sanctuary showed the trends of gradual decrease in floristic composition and phytodivesity status of three plantation sites (Tectona to Acacia to Eucalyptus) in respect to natural forest, which indicated that exotic tree plantations might have negative impact on floristic composition and phytodiversity of this semi-tropical forest area and the fast-growing exotic tree plantation of Acacia and Eucalyptus should be avoided for sustainable development of Rema-Kalenga wildlife sanctuary. Jahangirnagar University J. Biol. Sci. 3(2): 33-47, 2014 (December)